Assessment of the economic performance of the seabream and seabass aquaculture industry in the European Union. (July 2020) - Llorente, Ignacio; Fernández-Polanco, José; Baraibar-Diez, Elisa; Odriozola, María D.; Bjørndal, Trond; Asche, Frank; Guillen, Jordi; Avdelas, Lamprakis; Nielsen, Rasmus; Cozzolino, Maria; Luna, Manuel; Fernández-Sánchez, José L.; et al.
Abstract: Production of gilthead seabream ( Sparus aurata ) and European seabass ( Dicentrarchus labrax ) is the second most important aquaculture industry in the European Union in value terms. During the last 10 years, the industry has experienced a process of industry concentration with the aim to overcome efficiency and profitability issues. However, the economic performance of the companies is still in general rather poor. The present work analyzes the economic performance of EU seabream and seabass companies in the period 2008–2016. The work is the first study to analyze companies' profitability in the EU as a whole, by country and company size, using economic and financial data extracted from companies' annual accounts. Based on the results, the study discusses the improvement of production and business profitability in recent years and the different factors that may have caused it, as well as the challenges and threats that seabream and seabass companies will have to face in order to achieve economic sustainability. Highlights: Seabream-seabass companies profitability shows a positive evolution in recent years. There are positive effects of a greater company size on economic performance. We recommend policies focusing on increasing production value not just volume.